Implementasi Perda Nomor 7 Tahun 2002 terhadap Praktik Pelacuran dan Perbuatan Cabul di Kabupaten Gresik - Nadia Prawira Supriadi; Dodi Jaya Wardana; Ifahda Pratama Hapsari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to discuss the implementation issues of Gresik Regency Regional Regulation Number 7 of 2002 as an effort to overcome street prostitution. Gresik Regency, known as the City of Islamic Students, faces challenges related to prostitution practices. Although Gresik Regency only has the authority to regulate street prostitution, efforts were made by issuing Regional Regulation (Perda) Number 7 of 2002 concerning the Eradication of Prostitution and Indecent Acts in Gresik Regency. However, in its implementation, this Perda is considered ineffective in overcoming the growing number of street prostitution. Several problems emerged, including the implementation of the Perda and its level of success. The research method used is the sociological juridical method with data collection techniques through observation and interviews. The results of the study show that the Gresik Regency Satpol PP implemented Perda Number 7 of 2002 by conducting raids. However, the raids still face obstacles such as information leaks, limited authority, and military interference in prostitution efforts. In addition to raids, the authorities also provide an introduction to the Perda to prostitutes and pimps as a preventive measure. The analysis of the factors driving the effectiveness of the law shows that this Regional Regulation has not been implemented optimally. Inhibiting factors include law enforcement, public legal awareness, and cultural factors. The author recommends that the Gresik Regency Government conduct socialization of Regional Regulation Number 7 of 2002 to the public to improve understanding and legal awareness. In addition, Satpol PP needs to conduct routine raids in collaboration with the police to follow up on the involvement of military personnel and take firm action against civil servants who leak the implementation of raids. The public is also expected to support the authorities in overcoming prostitution